The Development of Attitudes Toward Scientific Models During a Participatory Modeling Process – The Impact of Participation and Social Network Structure - Goelz, Taylor; Hartley, Troy; Scheld, Andrew; Carboni, Inga (Frontiers in Marine Science, 2020)
Scientific models are increasingly being used to support participatory natural resources management decision making processes. These models allow stakeholders and scientists to explore potential policy and management options and can help facilitate discussion surrounding concerning uncertainty and different sources of knowledge. The unique benefits of participatory modeling processes, however, are contingent upon stakeholders understanding of, engagement with, and willingness to use the scientific models as sources of knowledge and information. Little is known, however, about how stakeholders view scientific models within these processes. We examined changes in stakeholders’ attitudes toward scientific models over the course of OysterFutures, a 2-year, facilitated participatory modeling process that aimed to create consensus recommendations for oyster management in the Choptank River Complex, MD, United States. Five ordered logistic regression models were used to test hypotheses concerning the impact of social network measures, factors related to the participatory modeling process itself, and stakeholder characteristics on salience, credibility and legitimacy (SCL) attitudes toward models. Results suggested that stakeholders’ ways of knowing was a significant driver of salience, credibility and legitimacy elements of attitudes toward models. Additionally, acting as a gatekeeper within the social network resulted in significantly lower attitudes toward model credibility. These results indicate that the scientific model acted as a boundary object that facilitated discussion during the participatory modeling process. By better understanding the factors that influence model attitude formation, these processes can adjust their design and function to better take advantage of these models. Additionally, practitioners can have more realistic expectations concerning the role of models within participatory, collaborative natural resources decision-making processes.